Water Level Control Sistem Otomatis Sederhana pada Tandon Air di Kawasan Perumahan - Afgan Suffan Aviv; Ari Wardayanti; Endah Budiningsih; Afni Kurnia Fimani; Bambang Suhardi (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2016)
Plenty of water and electricity are wasted in residential areas because people often forget turning off the water pump or do not know when the water tank is full. Solution of these problems is using a water level control as an automatic tool to turn off and turn on the water pump. However, the water level control that exist today has many shortcomings. It has a complicated operating system, especially for people in a residential area with a range of price more than IDR 50,000. So this study was conducted with the aim of simplifying the system of water level control so its price is more affordable and simple operation, knowing the working principle and study the effectiveness and efficiency. From the research that has been done resulting an automatic water level control with more simple system and a production cost of IDR 19,000 with a selling price of IDR 25.000.